(untitled) (LINGUISTICA, 2015)
Ellipsis is omission of words which has been understood well from the omission will not change the meaning of the utterance itself. We can find mostly ellipsis in spoken language. One of spoken languages we can use as the medium in learning ellipsis is movie script. One of many great movie scripts is The Fault in Our Stars movie script by Scott Neustadter& Michael H. Weber. The aim of the research is to find out the use of Ellipsis by ˜Hazel™ in The Fault in Our Stars movie script. This research is descriptive qualitative research since it analyzes the use of ellipsis by ˜Hazel™ in the movie script. The data are the ellipsis which are used by character ˜Hazel™ in each her utterances in The Fault in Our Stars movie script from 50 scenes. The result of the research shows there are three 124 utterances consist of 31 Nominal Ellipsis with 25%, 4 Verbal Ellipsis with 3.23%, and 89 Clause Ellipsis with 71.77%. The most dominant type of Ellipsis that used by character ˜Hazel™ in The Fault in Our Stars movie script is Clause Ellipsis with 89 total numbers and total percentages 71.77%. It means people in having conversation want to be as effective as possible since the most complex grammatical unit is a clause. From this research, I hope the readers, lecturers, and students should apply ellipsis appropriately in their daily conversation in order to avoid misunderstanding in the conversation since ellipsis appears mostly in the informal context and daily conversation.